Field‐Aligned GPS Scintillation: Multisensor Data Fusion. Issue 1 (29th January 2018) - Mrak, Sebastijan; Semeter, Joshua; Hirsch, Michael; Starr, Gregory; Hampton, Don; Varney, Roger H.; Reimer, Ashton S.; Swoboda, John; Erickson, Philip J.; Lind, Frank; Coster, Anthea J.; Pankratius, Victor
Abstract: The Mahali Global Positioning System (GPS) array (9 receivers, 15–30 km baseline distance) in central Alaska has probed auroral structures in a field‐aligned direction during a geomagnetic substorm on 7 October 2015. We present results from a collaborative study of GPS phase scintillation, optical emission brightness, and ionospheric density perturbations, by virtue of data fusion procedure from the Mahali GPS array, all‐sky imager (ASI), and the Poker Flat Incoherent Scatter Radar (PFISR). First, we present observations in a traditional way using colocated GPS‐ASI sensors, giving us a principal pattern of the phase scintillation with respect to auroral brightness, free of any mapping ambiguities. Next, we use an assumption that the plasma irregularities are located at an altitude of 120 km, we map the optical data to this altitude, and we extend the GPS‐ASI study over the entire field of view of the GPS receiver array. We obtain a repeatable and persuasive pattern, revealing that GPS phase scintillation is clustered at the auroral edges. Moreover, investigation of the colinear ISR observations supports the altitude assumption of scintillation producing irregularities, and PFISR‐derived electric field estimates suggest that the source for irregularities is gradient drift instability. The phase scintillation was observed on all GPS receivers, phase scintillation exceeded once cycle during several electrojet intensifications, and several events lasted for more than a minute. Finally, phase scintillation was observed during all surge events, independent of the particular auroral morphology. Key Points: Field‐aligned GPS phase scintillation abruptly arises right after the peak in auroral brightness and lasts throughout its trailing edge luminosity All receivers in the GPS receiver array experienced coherent scintillation, caused by successive westward traveling surges Joint GPS‐ASI‐ISR observations suggest that E region electrodynamic processes are sources of resulting plasma irregularities